2007
DOI: 10.1007/s10995-006-0171-2
|View full text |Cite
|
Sign up to set email alerts
|

Child Injury Risks are Close to Home: Parent Psychosocial Factors Associated with Child Safety

Abstract: Objective: In several populations, maternal depression has been associated with reduced child safety. In an urban pediatric Emergency Department, we examined the relationship between parental depression, social support, and domestic conflict and child safety behaviors.Methods: We studied consecutive patients in an Emergency Department. Trained interviewers used a structured instrument to assess patient, primary caregiver, and household demographics, socio-economic status, psychosocial factors, child safety beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
13
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 45 publications
6
13
1
2
Order By: Relevance
“…Our study shows that 34% of the households had chemicals that were kept locked up, which is comparable to a study from the USA, where this percentage is said to be between 26% and 32% 20. However, another study from the USA showed that in 4.3% of the households not all the chemicals were locked up,23 which is in contrast with our finding. A Singaporean study showed comparable risks for sharp furniture 7…”
Section: Discussionsupporting
confidence: 55%
“…Our study shows that 34% of the households had chemicals that were kept locked up, which is comparable to a study from the USA, where this percentage is said to be between 26% and 32% 20. However, another study from the USA showed that in 4.3% of the households not all the chemicals were locked up,23 which is in contrast with our finding. A Singaporean study showed comparable risks for sharp furniture 7…”
Section: Discussionsupporting
confidence: 55%
“…Parental factors such as supervision,35 risk taking behaviours,36 37 ability to match children's capabilities to tasks, wanting to foster independence in their children, ability to recognise hazards,38 maternal depression and social support39 are associated with childhood injuries and may also be socially distributed. Further research into these areas (and how they might interact with the home environment) could help establish why inequalities in injuries persist and contribute to the design or adaptation of policies to reduce them.…”
Section: Discussionmentioning
confidence: 99%
“…The association remains significant even after adjusting for confounders, including young maternal age, marital status, social support status, maternal psychiatric history, or economic situation. Previous studies reported that younger maternal age [9], single-parent families [8], lack of social support [25], and low economic status [26], were associated with unintentional injury among infants and toddlers. Further, maternal depression has been previously linked to occurrences of injury among infants and toddlers [13].…”
Section: Discussionmentioning
confidence: 99%